Factors affecting the use risk-based audit approach - Đặng Anh Tuấn (Tạp chí Khoa học Đại học Mở Thành phố Hồ Chí Minh - Kinh tế và Quản trị kinh doanh, 2024)
The business risk approach to auditing is familiar in the private sector. However, this approach is relatively new to auditing in the public sector in many countries, including Vietnam. This study aims to explore the predictive model of factors affecting the application of risk approach in auditing (RBA) and audit quality. Research data was collected by surveying 211 state auditors through SEM linear structure analysis with SmartPLS 4.0.8.5 software. The research results show that the risk of the audited entity and the application of Information Technology (IT) have a positive and significant impact on the audit risk approach and contribute to the assurance of audit quality in the State Audit. This implies that with IT support, the application of RBA will become effective in improving audit efficiency and quality assurance.